Epidemiological Profile of Ascariasis in Provincial General Reference Hospital of Kinshasa, Democratic Republic of the Congo - Motuta Amisi Christian; Djolu Djoza Ruphin; Masengo Ashande Colette; Gbolo Zoawe Benjamin; Bongo Ngiala Gédéon; Lengbiye Moke Emmanuel; Mbembo-Wa-Mbembo Blaise; Koto-te-Nyiwa Ngbolua (Britain International of Exact Sciences (BIoEx) Journal, 2020)
A cross sectional study was carried out on intestinal ascariasis, which is a helminth of fecal peril that colonizes the digestive tract with the possibility of complications in organs such as the intestines, liver, lungs and even the brain. The study was carried out at the General Reference Hospital of Kinshasa where medical records were used to collect data and the study period was from January 2016 and December 2017. The findings show females (61.19%) are predominant than males (38.80%), and the gender sex ratio (M/F) was 0.63. The incidence was high in June 2016 and November 2017 are the most affected months by Ascariasis in our study with 7 cases or 18.98% and 6 cases or 20% for each year. The age group between 31 - 40 years of age predominated by the attack of this parasitic affection with the extreme ages of 8 months and 75 years. The incidence varied with a peak in June with 7 cases or 18.98%. A variable incidence with a peak in November with 6 cases or 20%.